Integrasi Simulasi PhET dalam Pembelajaran Mendalam pada Materi Fisika SMP - Maria Felniani Purnasari Adur; Egidius Dewa; Maria Febriani Nada (Kilau Publishing, 2025)
Low students’ conceptual understanding of force and Newton’s Laws remains a major problem in junior high school physics learning due to the abstract nature of the concepts and the limited use of visual learning media. This study aimed to analyze the improvement of students’ understanding of force and Newton’s Laws after the implementation of PhET simulations within a deep learning-oriented instructional framework. This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 25 seventh-grade students at SMPK Adisucipto Penfui. The research instrument was a test of students’ conceptual understanding of force and Newton’s Laws. Data were analyzed using descriptive statistics and N-Gain analysis. The results showed an average pretest score of 64.64 and a posttest score of 81.56, with a mean N-Gain of 0.532 (moderate category). These findings indicate an improvement in students’ conceptual understanding after PhET-based learning. However, the results are still limited by the absence of a control group.